Multi-objective analysis of train operations using simulation - Jimenez, Koshneir Sarte
With the worsening traffic condition in Metro Manila and in other urban centers, the country faces a growing need for higher capacity and more efficient transportation. Among the best solutions for the traffic congestion problem in the Philippines is the construction of railway systems that could meet the present and future demands of transportation. In this study, a simulation program was developed that is able to provide data on the movement of trains. The data was then processed to determine delay, passenger capacity and power consumption of the railway vehicles in a double-track railway system. The output of the research was a tool for analyzing current railway systems in terms of capacity and an aid to transport planners in the improvement and further development of the future railway systems. The input parameters of the program was the infrastructure (stations, station distances and blocking distances), the railway vehicle characteristics (train cars, passenger capacity, speed, acceleration, etc) and the passenger demand. The primary independent variables for the tests were: (a) the speed of the trains, which determines the blocking distances and the minimum headway; and (b) the number of trains, which determines the headway, in the system. As the number of trains and headway increased with different speeds and blocking distances, the simulation program and the data processing algorithm generated the following parameters: (a) the delay increase in the operation of the trains; (b) the number of passengers served by the railway system; and (c) the power consumption the railway vehicles (obtained from Davis formula) The case study for the research was the Manila Metro Rail Transit System (MRT-3) Line 3 along EDSA. The simulation program used a headway range setting from 1 minute to 9 minutes, which includes the minimum and the maximum operational headway data available from the Department of Transportation. The speed setting were varied from 20 kph, the slowest train speed recorded, to 65 kph, the design speed of the trains. The number of trains used was set from the minimum to the maximum allowable by the blocking distance settings. The result showed a significant improvement of capacity by increasing speeds, up to 15% with decreased in power consumption, and decrease in delay - average of 20% (up to saturation), compared to the alternative solution of increasing the number of trains.